Investigation of premenstrular dysphoric disorder comorbidity and related factors in patients with anxiety disorder - Soyak, Huda Murat; Acmaz, Gokhan; Uguz, Faruk (Annals of Medical Research, 2021)
Aim: Because of the fact that the frequency of both anxiety disorders and premenstrual dysphoric disorder (PMDD) are high in women and that studies investigating PMDD comorbidity in patients diagnosed with anxiety disorder are limited, this study was aimed to investigate PMDD comorbidity and related factors in patients with anxiety disorders.Materials and Methods: 183 subjects who were followed up with a diagnosis of anxiety disorder in Necmettin Erbakan University Meram Medical Faculty Psychiatry Outpatient Clinic were included in the study and were evaluated with Sociodemographic Data Form, Beck Anxiety Inventory (BAI) and Beck Depression Inventory (BDI). PMDD comorbidity was investigated according to The Diagnostic and Statistical Manual of Mental Disorders fourth edition (DSM-IV-TR) criteria by making psychiatric interviews.Results: 57 (31.2%) of 183 subjects diagnosed with PMDD constituted the PMDD group and the remaining 126 patients constituted the non-PMDD group. The mean BAI scores of the PMDD group were significantly higher than those of the non PMDD group, whereas the mean age of the PMDD group was significantly lower than that of the non PMDD group. The BMI of the PMDD group was significantly higher than that of the non PMDD group.Conclusion: PMDD is common in patients followed up with a diagnosis of anxiety disorder and what is associated with PMDD is be young age as well as excessive chocolate consumption.
Keywords: Anxiety disorders; premenstrual dysphoric disorder; premenstrual syndrome